Metal particle

Metal particles with intermetallic compound crystals in a Sn and Sn-Cu alloy matrix address the challenge of high heat resistance and bonding strength for next-generation power semiconductors, enabling reliable bonding with aluminum under extreme temperature conditions.

JP2025037692AActive Publication Date: 2025-03-18NAPRA +1

Patent Information

Application Number
JP2023144780
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-18
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

Existing bonding materials for next-generation power semiconductors like SiC and GaN lack high heat resistance and mechanical strength, especially under severe temperature fluctuations, and cannot bond effectively with aluminum.

Method used

Metal particles with intermetallic compound crystals containing Sn, Cu, Ni, Al, and Cr in a matrix of Sn and Sn-Cu alloy, which provide enhanced bonding strength and heat resistance, and can bond with aluminum.

Benefits of technology

The metal particles maintain excellent bonding strength and mechanical strength even under extreme temperature variations, enabling reliable bonding with aluminum and supporting the high heat resistance required for next-generation power semiconductors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037692000001_ABST
    Figure 2025037692000001_ABST
Patent Text Reader

Abstract

To provide metal particles capable of maintaining superior bonding strength and mechanical properties, even under harsh thermal variations in extreme high- or low-temperature environments, by overcoming the inherent brittleness of intermetallic compounds.SOLUTION: The present invention provides metal particles that comprise intermetallic compound crystals comprising Sn, Cu, Ni, Al, and Cr within a matrix phase comprising Sn and a Sn-Cu alloy, wherein the composition of the metal particles comprises Cu: 0.7-15 mass%, Ni: 1-0.02 mass%, Al: 3-0.02 mass%, Cr: 2-0.02 mass%, and the balance being Sn, wherein the composition of the matrix phase comprises Sn: 92-99.9 mass%, Cu: 5 mass% or less, Ni: 1 mass% or less, and Al: 3 mass% or less, and wherein the composition of the intermetallic compound comprises Cu: 5-50 mass%, Ni: 6.5-0.1 mass%, Al: 20-0.5 mass%, Cr: 0.001-0.1 mass%, and the balance being Sn.SELECTED DRAWING: Figure 4B
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to metal particles. [Background technology]

[0002] As the Internet of Things (IoT) advances and greater energy conservation is required, the importance of power semiconductors, which are the core of the technology, is increasing. However, there are many challenges to their use. Power semiconductors generate a lot of heat and reach high temperatures due to the high voltage and current they handle and the ultra-high speed transmission. The heat resistance required for current Si power semiconductors is approximately 175°C, but Si power semiconductors that can withstand temperatures of approximately 200°C are being developed. In addition, next-generation power semiconductors such as SiC and GaN will be required to use gold on the front and back of the device for high-speed communication transmission, maintain their transmission characteristics, and endure extremely high temperatures of 250 to 500°C.

[0003] On the other hand, when it comes to bonding materials, there are no bonding materials that have the high heat resistance required for next-generation power semiconductors such as the above-mentioned SiC and GaN. For example, the SnAgCu-based bonding material (powder solder material) disclosed in Patent Document 1 is only applicable to power semiconductors compatible with temperatures of approximately 125° C., and cannot be applied to next-generation power semiconductors. Furthermore, there is a problem in that conventional solder bonding materials cannot be bonded to aluminum.

[0004] Meanwhile, the present applicant has proposed metal particles in Patent Document 2, which are composed of an outer shell and a core portion, the core portion containing a metal or alloy, the outer shell being made of a mesh of an intermetallic compound and covering the core portion, the core portion containing Sn or an Sn alloy, and the outer shell containing an intermetallic compound of Sn and Cu. The joint formed by these metal particles can maintain high heat resistance, joint strength, and mechanical strength for a long period of time, even when a high-temperature operating state continues for a long period of time, or even when used in a harsh environment, such as when a large temperature fluctuation occurs from a high-temperature operating state to a low-temperature stopped state. However, intermetallic compounds have a drawback in that they are brittle. If this problem could be solved, it would be possible to provide a bonding material having even higher heat resistance, bonding strength and mechanical strength.

[0005] Therefore, the present applicant further proposed in Patent Document 3 that a matrix containing Sn and a Sn-Cu alloy has an intermetallic compound consisting of Sn, Cu and Ni, and at least a part of the Sn-Cu alloy and the intermetallic compound in the matrix is ​​endotaxy bonded. However, it was found that in a heating atmosphere of 260°C or higher, the matrix surrounding the intermetallic compound shrinks, causing the endotaxial bond to collapse and promoting the generation of voids. Therefore, when used in a harsh environment at high temperatures, there is a risk that high heat resistance, bonding strength and mechanical strength cannot be maintained for a long period of time. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2007-268569 A [Patent Document 2] Patent No. 6029222 [Patent Document 3] Patent No. 6799649 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide metal particles which can overcome the brittleness of intermetallic compounds and maintain excellent bonding strength and mechanical strength even under severe temperature fluctuations in extremely high or low temperature environments, and which can be bonded to aluminum. [Means for solving the problem]

[0008] The present invention relates to metal particles having an intermetallic compound crystal containing Sn, Cu, Ni, Al and Cr in a matrix containing Sn and a Sn-Cu alloy, The composition of the metal particles is Cu 0.7~15% by mass, Ni 1~0.02% by mass, Al 3~0.02% by mass, Cr 2~0.02% by mass, The balance is Sn (provided that, when unavoidable impurities are present, the unavoidable impurities are 0.1 mass% or less); The composition of the parent phase is Sn 92~99.9% by mass, Cu 5% by mass or less, Ni 1% by mass or less, Al is 3% by mass or less (however, when unavoidable impurities are present, the unavoidable impurities are 0.1% by mass or less); The composition of the intermetallic compound is Cu 5~50% by mass, Ni 6.5~0.1% by mass, Al 20~0.5% by mass, Cr 0.001~0.1% by mass, The balance is Sn (provided that, when unavoidable impurities are present, the unavoidable impurities are 0.1 mass% or less); The intermetallic compound crystals are present in the matrix. The present invention provides metal particles characterized by the above. The present invention also provides a consolidated body made of the metal particles described in 1 above. Effect of the Invention

[0009] According to the present invention, it is possible to overcome the brittleness of intermetallic compounds and maintain excellent bonding strength and mechanical strength even in the face of severe temperature fluctuations in extremely high or low temperature environments, and it is also possible to provide metal particles and consolidated bodies that can be bonded to aluminum. The inventors have conducted extensive research and found that the metal particles of the present invention have a characteristic structure in which intermetallic compound crystals containing Sn, Cu, Ni, Al, and Cr are contained in a matrix containing Sn and an Sn-Cu alloy by producing the metal particles from raw materials having a composition consisting of Cu, Ni, Al, Cr, and the remainder Sn, based on the production method under the following conditions. The metal particles and the solidified body obtained by solidifying the metal particles allow the adjustment of the solid phase and liquid phase temperatures of the metal, and the presence of Al in the intermetallic compound crystals makes it possible to bond between Al and other metals, which was previously impossible, and the above-mentioned intermetallic compounds can solve problems caused by the brittleness and maintain excellent bonding strength and mechanical strength. [Brief description of the drawings]

[0010] [Figure 1] 1 is a STEM image of a cross section of a solidified body made of metal particles of the present invention obtained in Example 1, which was thinly cut with a FIB (focused ion beam). [Diagram 2] FIG. 2 is a diagram for explaining an example of a manufacturing apparatus suitable for manufacturing the metal particles of the present invention. [Figure 3A] FIG. 2 is a diagram showing the results of element mapping analysis by EDS of the cross section of metal particle 1 obtained in Example 1. [Figure 3B] FIG. 2 is a diagram showing the results of element mapping analysis by EDS of the cross section of metal particle 1 obtained in Example 1. [Figure 4A] In the joint structure in Example 2, (a) is an SEM image of a cross section of the joint surface between the plating layer surface 120 of the copper clip and the aluminum surface 140 on the Si chip, and (b) is an enlarged view. [Figure 4B] 4B is a further enlarged photograph of the joint portion C in FIG. 4A. [Diagram 5] FIG. 2 is a schematic cross-sectional view for explaining the structure of a joint structure portion in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will now be described in further detail. First, the terminology used in this specification is as follows unless otherwise specified. (1) The term "metal" refers not only to single metallic elements, but also to alloys and intermetallic compounds containing multiple metallic elements. (2) When referring to a single metal element, it does not mean only a substance that is completely and purely made of the metal element, but also means a case where it contains a small amount of other substances. In other words, it does not mean to exclude a substance that contains a small amount of impurities that have almost no effect on the properties of the metal element, and for example, when referring to a parent phase, it does not mean to exclude a substance in which some of the atoms in the Sn crystal are replaced by other elements (e.g., Cu). For example, the other substances or other elements may be contained in the metal particles in an amount of 0 to 0.1 mass %.

[0012] The metal particles and consolidated body using the same according to the present invention are characterized in that they have intermetallic compound crystals containing Sn, Cu, Ni, Al and Cr in a matrix containing Sn and a Sn-Cu alloy.

[0013] Fig. 1 is a STEM image of a cross section of a solid formed using the metal particles of the present invention obtained in Example 1 below, thinly cut by FIB (focused ion beam). Referring to the solid made of metal particles in Fig. 1, the metal particles have intermetallic compound crystals (dark colored parts) containing Sn, Cu, Ni, Al and Cr in a matrix (light colored parts) containing Sn and a Sn-Cu alloy. The particle diameter of the metal particles of the present invention is preferably in the range of 1 μm to 50 μm, for example, and the solid made of the metal particles of the present invention has a thickness of 10 mm or less.

[0014] The metal particles of the present invention may have a composition, for example, Cu 0.7~15% by mass, Ni 1~0.02% by mass, Al 3~0.02% by mass, Cr 2~0.02% by mass, The balance is Sn, provided that, when unavoidable impurities are present, the amount of said unavoidable impurities is 0.1 mass % or less.

[0015] The metal particles of the present invention can be produced from raw materials having a composition of, for example, 8% by mass of Cu, 1% by mass of Ni, 1% by mass of Al, 1% by mass of Cr, and the balance being Sn, by melting the raw materials, feeding them onto a dish-shaped disk rotating at high speed in a nitrogen gas atmosphere, scattering the molten metal as small droplets by centrifugal force, and cooling and solidifying them under reduced pressure. Furthermore, the consolidated body of the present invention (hereinafter sometimes referred to as bulk) can be obtained by directly inserting the metal particles of the present invention into a rolling rotary roll heated to 100°C to 190°C and processing it, and the bulk has a shape of, for example, a sheet, and multiple sheets of this may be laminated. The present inventors have confirmed that the structure of the metal particles of the present invention is maintained even after bulking.

[0016] An example of a manufacturing apparatus suitable for manufacturing the metal particles of the present invention will be described with reference to FIG. 2. The granulation chamber 1 has a cylindrical upper portion and a cone-shaped lower portion, and has a lid 2 on the upper portion. A nozzle 3 is inserted vertically into the center of the lid 2, and a dish-shaped rotating disk 4 is provided directly below the nozzle 3. Reference numeral 5 denotes a mechanism for supporting the dish-shaped rotating disk 4 so that it can move up and down. An exhaust pipe 6 for the generated particles is connected to the lower end of the cone part of the granulation chamber 1. The upper portion of the nozzle 3 is connected to an electric furnace (high-frequency furnace: conventionally, a ceramic crucible was used, but in the present invention, a carbon crucible is used) 7 for melting the metal to be granulated. Ambient gas adjusted to a predetermined composition in a mixed gas tank 8 is supplied to the inside of the granulation chamber 1 and the upper portion of the electric furnace 7 through pipes 9 and 10, respectively. The pressure in the granulation chamber 1 is controlled by a valve 11 and an exhaust device 12, and the pressure in the electric furnace 7 is controlled by a valve 13 and an exhaust device 14, respectively. Molten metal fed from nozzle 3 onto dish-shaped rotating disk 4 is broken into fine droplets by the centrifugal force of dish-shaped rotating disk 4, which then scatter and cool under reduced pressure to form solid particles. The solid particles thus produced are fed from discharge pipe 6 to automatic filter 15 for sorting. Reference numeral 16 denotes a fine particle collector.

[0017] The process of cooling and solidifying the molten metal from a high temperature melt is important for forming the metal particles of the present invention. For example, the following conditions may be mentioned: The melting temperature of the metal in the melting furnace 7 is set to 600° C. to 800° C., and while maintaining this temperature, the molten metal is supplied from the nozzle 3 onto the dish-shaped rotating disk 4 . The dish-shaped rotating disk 4 used is a dish-shaped disk having an inner diameter of 35 mm and a rotor thickness of 5 mm, and is rotated at 80,000 to 100,000 revolutions per minute. Granulation chamber 1: 9 x 10 -2 After reducing the pressure in the granulation chamber 1 using a vacuum chamber capable of reducing the pressure to about 1×10 Pa, nitrogen gas at 15 to 50° C. was supplied while simultaneously evacuating the gas. -1 Pa or less.

[0018] The composition of the matrix in the metal particles of the present invention is Sn 92~99.9% by mass, Cu 5% by mass or less (e.g. 0.02-5% by mass), Ni 1 mass% or less (e.g., 0.02 to 1 mass%), The Al content is 3 mass % or less (for example, 0.02 to 3 mass %), and when unavoidable impurities are present, the content is preferably 0.1 mass % or less.

[0019] The composition of the intermetallic compound crystal in the metal particles of the present invention is as follows: Cu 5~50% by mass, Ni 6.5~0.1% by mass, Al 20~0.5% by mass, Cr 0.001~0.1% by mass, The balance is preferably Sn. When unavoidable impurities are present, their content is preferably 0.1 mass % or less. The ratio of the intermetallic compound in the metal particles of the present invention is, for example, 20 to 60 mass %, and preferably 30 to 40 mass %, based on the entire metal particles. The intermetallic compound is present in a state of being included in the matrix.

[0020] The composition and ratio of the matrix and intermetallic compounds can be satisfied by complying with the manufacturing conditions of the metal particles.

[0021] When the metal particles of the present invention are used as a bonding material to bond Al and other metals, the bonding can be achieved, for example, by the following method (1). (1) A method in which a plating layer made of the metal particles of the present invention is formed on the other metal, and then ultrasonic waves are applied between Al and the plating layer. The plating layer may be formed according to the method described in Japanese Patent No. 7323979, for example, and will be described below. The other metal (for example, copper, a copper alloy, or stainless steel) is used as a substrate. Meanwhile, an electrode for electrolytic plating is prepared using the metal particles of the present invention, and a plating layer is formed on the surface of the substrate. The electrolytic plating electrode may be a soluble electrode, and may be produced by the following method. First, the metal particles of the present invention are produced. Then, the obtained metal particles of the present invention are melted by high-frequency induction heating under vacuum, cast into a mold in a nitrogen gas atmosphere under atmospheric pressure, and cooled and solidified to form a rolled sheet. The high-frequency induction heating and cooling / solidifying conditions are, for example, as follows. High frequency induction heating: 9×10 -2 A crucible for high-frequency melting is placed in a vacuum chamber capable of reducing the pressure to about Pa, and the metal particles of the present invention are introduced into the crucible. While the pressure is reduced to about the aforementioned reduced pressure level, high-frequency induction heating is performed on the metal particles of the present invention, the heating temperature is increased to 800°C to 1000°C to melt the metal particles of the present invention, and the temperature is maintained for 5 to 15 minutes. Cooling and solidification: Next, while flowing nitrogen gas at 15 to 50°C into the tank, the heating temperature is set to about 400°C or higher under atmospheric pressure, casting is performed, and the mixture is cooled and solidified at 30°C or lower. The composition of the electrolytic plating electrode is the same as that of the metal particles of the present invention, that is, even when the electrolytic plating electrode is produced as described above, the structure and composition of the metal particles of the present invention are maintained in the same manner. Subsequently, when electrolytic plating is performed using the electrolytic plating electrode as an anode, the intermetallic compound crystals contained in the electrolytic plating electrode are dispersed in the plating bath in nano-sized crystals (1 μm or less), and are plated on the substrate surface together with the parent phase with an electric charge to form a plating layer. The formed plating layer also maintains the same structure and composition as the metal particles of the present invention. The plating bath contains the metal particles of the present invention, and the intermetallic compound crystals are dispersed in nano-size (1 μm or less) and plated onto the other metal together with the parent phase with an electric charge to form a plating layer. The formed plating layer has the same composition as the metal particles of the present invention.

[0022] The plating bath for providing the plating layer may have, for example, the following composition in addition to containing the electrolytic plating electrode. Copper sulfate 180~250g / L Stannous sulfate 30~50g / L Sulfuric acid 80~120g / L Additives, etc. (adhesion inhibitors, interface complexing agents, film forming agents, electrodiffusion wear forming agents) In addition to the above-mentioned exemplary components of the plating bath, known dispersants, brighteners, antioxidants, etc. may be appropriately added as necessary. Examples of such agents include dispersants such as polyoxyethylene cumyl phenyl ether and polyoxyethylene lauryl ether, brighteners such as cresol sulfonic acid, acetaldehyde, and acetylacetone, and antioxidants such as formalin, catechol, and hydroquinone. The plating temperature is, for example, 30°C or lower, and is preferably 15 to 20°C. The current density is, for example, 1 to 10 A / dm 2 The range is appropriately adjusted.

[0023] The plated substrate is then heat-treated, for example at a temperature of 100 to 300° C. and for a heating time of, for example, about 5 to 30 seconds. By the above operations, a plating layer is formed on the surface of the base material. The thickness of the plating layer is, for example, 2 μm to 10 μm.

[0024] The conditions for applying ultrasonic waves (ultrasonic welding) between the Al and the plating layer may be any known conditions as appropriate, and examples include frequency: 20 to 110 kHz, oscillation mode: 20 to 500 ms, load range: 5 N to 1000 N, oscillation range: X350 mm × Y100 mm, etc.

[0025] When joining a metal other than Al to the above-mentioned other metals, the joining conditions such as heating may be in accordance with ordinary methods.

[0026] The bulk of the present invention can be obtained by directly inserting metal particles into a rolling rotary roll heated to 100°C to 190°C as described above and processing the same. The bulk has a shape of, for example, a sheet, and multiple sheets of the sheet may be laminated. The bulk of the present invention, for example, when combined with Cu, Ni alloy particles, or hydrogenated Ti powder, which have higher electrical conductivity than Sn, and the metal particles of the present invention (IMC particles), has good electrical conductivity and suppresses volume change over a relatively wide temperature range, making it possible to produce heterogeneous bonding material sheets such as ceramics, and it is also possible to obtain a substrate that functions as a bonding material with heat dissipation capabilities.

[0027] Moreover, the metal particles of the present invention can be mixed in an organic vehicle to obtain a conductive paste.

[0028] The bulk or the conductive paste may contain other particles such as SnAgCu alloy particles, Cu, Cu alloy particles, Ni, Ni alloy particles, or a mixture thereof, and may be mixed with metal particles. These other particles may be coated with a metal such as Si, if necessary. For example, by combining Cu or Ni alloy particles, which have higher electrical conductivity than Sn, with metal particles, a metal bonding layer can be obtained that has good electrical conductivity and is suppressed from changing in volume over a relatively wide temperature range.

[0029] By using the metal particles of the present invention, a joint structure capable of enjoying the effects of the metal particles as they are can be obtained. FIG. 5 is a schematic cross-sectional view for explaining the structure of a joint structure in the present invention. In Fig. 5, the joining structure joins metal / alloy bodies 101, 501 (one is Cu and the other is Al in Fig. 5) formed on opposing substrates 100 (e.g. Cu) and 500 (e.g. chip). A diffusion phase 300 of different metals is formed by the metal particles of the present invention, and the diffusion phase 300 constitutes the main component of the joining structure.

[0030] The substrate 100, 500 is a substrate equipped with a semiconductor element and constituting an electronic or electrical device such as a power device, and the metal / alloy body 101, 501 is a connection member integrally provided on the substrate 100, 500 as an electrode, bump, terminal or lead conductor.

[0031] The inventors have confirmed that the bonded structure obtained after heating using the metal particles of the present invention has a crystal structure similar to the crystal structure of the metal particles (however, when the metal / alloy body 101, 501 contains Cu, Cu is further added to the bonded structure).

[0032] The joint structure of the present invention has an intermetallic compound crystal containing Sn, Cu, Ni, Al and Cr in a matrix containing Sn and an Sn-Cu alloy, The composition of the joint structure is Cu 0.7~15% by mass, Ni 1~0.02% by mass, Al 3~0.02% by mass, Cr 2~0.02% by mass, The balance is Sn (provided that, when unavoidable impurities are present, the unavoidable impurities are 0.1 mass% or less); The composition of the parent phase is Sn 92~99.9% by mass, Cu 5% by mass or less, Ni 1% by mass or less, Al is 3% by mass or less (however, when unavoidable impurities are present, the unavoidable impurities are 0.1% by mass or less); The composition of the intermetallic compound is Cu 5~50% by mass, Ni 6.5~0.1% by mass, Al 20~0.5% by mass, Cr 0.001~0.1% by mass, The balance is Sn (however, in the case where unavoidable impurities are present, the amount of said unavoidable impurities is 0.1 mass % or less). In the joint structure, the intermetallic compound is present in a state of being contained in the parent phase.

[0033] The ratio of the intermetallic compound in the joint structure of the present invention is, for example, 20 to 60 mass %, and preferably 30 to 40 mass %, relative to the joint structure. EXAMPLES

[0034] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0035] Example 1 The raw material had a composition of 8 mass % Cu, 1 mass % Ni, 1 mass % Al, 1 mass % Cr, and the remainder Sn, and metal particles 1 having a diameter of about 3 to 13 μm were produced by the production apparatus shown in FIG. In this case, the following conditions were adopted: A melting crucible was placed in a melting furnace 7 , the above-mentioned raw materials were placed therein, and melted at 650° C. While maintaining that temperature, the molten metal was supplied from the nozzle 3 onto the dish-shaped rotating disk 4 . The dish-shaped rotating disk 4 used was a dish-shaped disk having a diameter of 35 mm and a rotating disk thickness of 3 to 5 mm, and was rotated at 80,000 to 100,000 revolutions per minute. Granulation chamber 1: 9 x 10 -2 After reducing the pressure in the granulation chamber 1 using a vacuum chamber capable of reducing the pressure to about 1×10 Pa, nitrogen gas at 15 to 50° C. was supplied while simultaneously evacuating the gas. -1 Pa or less.

[0036] The obtained metal particle 1 has a cross section as shown in FIG. 1. When element mapping analysis of the cross section of the metal particle 1 was performed by EDS (see FIGS. 3A and 3B), the composition of the metal particle was Cu 8.08% by mass, Ni 2.42% by mass, Al 1.65% by mass, Cr 1.68% by mass, The remainder was found to be Sn. The composition of the parent phase is: Sn 94.55% by mass, Cu 4.73% by mass, Ni 0.71% by mass, Al 0.11% by mass, It turned out to be. The composition of the intermetallic compound crystal is as follows: Cu 18.49% by mass, Ni 7.71% by mass, Al 19.58% by mass, Cr 0.98% by mass, The remainder was found to be Sn.

[0037] The intermetallic compounds in the metal particles 1 accounted for 30 to 35 mass % of the metal particles.

[0038] Next, the metal particles 1 were dry-powder pressed to create a sheet, and this sheet was used to join a Cu electrode and a Cu substrate to form a joint structure. A high-temperature test (HTS) was then performed at 260°C. The test results showed that the shear strength increased from approximately 50 MPa to approximately 60 MPa from the start of the test up to approximately 100 hours, and stabilized at approximately 60 MPa in the time range over 100 hours. In addition, in a thermal cycle test (TCT) (-40 to 200°C), the test results showed that the shear strength was stable at approximately 50 MPa over the entire cycle (1,000 cycles). The sheet had a cross section as shown in FIG. 1, and showed the same results as element mapping analysis of the cross section of the metal particle 1 by EDS.

[0039] Example 2 Metal particles 1 were produced using raw materials having a composition of 8 mass% Cu, 1 mass% Ni, 1 mass% Al, 1 mass% Cr, and the remainder Sn under the same conditions as in Example 1. Subsequently, an electrode for electrolytic plating was produced using the obtained metal particles 1. In this case, the following conditions were adopted: High frequency induction heating: 9×10 -2 A crucible for high-frequency melting was placed in a vacuum chamber capable of reducing the pressure to about Pa, and the metal particles 1 of the present invention were introduced into the crucible. While the pressure was reduced to about the above-mentioned reduced pressure level, high-frequency induction heating was performed on the metal particles 1 of the present invention, the heating temperature was raised to 900°C to melt the metal particles of the present invention, and the temperature was maintained for 5 minutes. Cooling and solidification: Next, while nitrogen gas at 15 to 50°C was flowed into the tank for 10 minutes, the heating temperature of the raw material was set to about 400°C under atmospheric pressure, the mixture was poured into a mold, and then cooled and solidified at room temperature. The obtained material was rolled into a sheet to obtain a metal sheet 2 having a thickness of 300 μm. This was used as an electrode for electrolytic plating in Example 2 and was placed in the following plating bath.

[0040] The obtained electrolytic plating electrode of Example 2 had a cross section as shown in Fig. 1. Furthermore, element mapping analysis of one cross section of the electrolytic plating electrode was performed by EDS. Cu 8.08% by mass, Ni 2.42% by mass, Al 1.65% by mass, Cr 1.68% by mass, The remainder was found to be Sn. The composition of the parent phase is: Sn 94.55% by mass, Cu 4.73% by mass, Ni 0.71% by mass, Al 0.11% by mass, It turned out to be. The composition of the intermetallic compound crystal is as follows: Cu 18.49% by mass, Ni 7.71% by mass, Al 19.58% by mass, Cr 0.98% by mass, The remainder was found to be Sn. Moreover, the intermetallic compound crystals in the electrolytic plating electrode accounted for 30 to 35 mass %.

[0041] A copper clip (copper plate) was used as the substrate (cathode). The substrate was subjected to electrolytic plating using the above-mentioned electrode for electrolytic plating under the following conditions to obtain a plated sheet metal.

[0042] Plating bath composition (concentration per liter of water): Copper sulfate 180~250g / L Stannous sulfate 30~50g / L Sulfuric acid 80~120g / L In addition, a known reference electrode was used, and an appropriate amount of additive was added. Plating temperature: 70℃ Current density: 3A / dm 2 Heat treatment temperature of the substrate after plating: 200℃ Heat treatment time of the substrate after plating: 300 seconds (in nitrogen atmosphere)

[0043] The composition of the resulting plating layer was the same as that of the electrolytic plating electrode of the present invention.

[0044] Next, the copper clip having the obtained plating layer on its surface and the aluminum surface on the Si chip were ultrasonically welded under the following conditions: frequency: 80 kHz, oscillation mode: 80% (8 levels, 25 to 500 ms). A high temperature test (HTS) was conducted at 260°C to measure the adhesion strength between the surface of the plating layer of the obtained copper clip and the aluminum surface on the Si chip. The test results showed that the shear strength increased from approximately 70 MPa to approximately 75 MPa from the start of the test up to approximately 100 hours, and then stabilized at approximately 75 MPa in the time range over 100 hours. Additionally, in thermal cycle testing (TCT) at -40 to 200°C, the test results showed that the shear strength remained stable at approximately 70 MPa over the entire cycle (1,000 cycles). Fig. 4A(a) is an SEM image of the cross section of the bonding surface between the plating layer surface 120 of the copper clip and the aluminum surface 140 on the Si chip, and Fig. 4A(b) is an enlarged view. Fig. 4B shows a further enlarged view of the bonding portion C. Fig. 4B shows that the diffusion of different metals is taking place.

[0045] Comparative Example 1 As a comparative example, a conventional SnAgCu-based bonding material (powder solder material with a particle size of 5 μm) was used and subjected to a thermal cycle test (TCT) of Example 1 (-40 to 200°C). The bonding portion collapsed within 100 cycles, and it was impossible to obtain the heat resistance and strength of the metal particles of the present invention. The inventors have confirmed through their investigations that conventional SnAgCu based bonding materials do not contain intermetallic compounds, but contain dispersed elements of a single metal.

[0046] Although the present invention has been described in detail above with reference to the accompanying drawings, the present invention is not limited thereto, and it is obvious that a person skilled in the art can conceive of various modifications based on the basic technical ideas and teachings thereof. [Explanation of symbols]

[0047] 1 Granulation chamber 2 lid 3 Nozzles 4-plate rotating disc 5 Rotating disk support mechanism 6 Particle discharge pipe 7. Electric Furnace 8 Mixed Gas Tank 9 Piping 10 Piping 11 Valve 12 Exhaust system 13 Valve 14 Exhaust system 15 Automatic Filter 16. Particle collection device 100 Substrates 101 Metal / Alloy Body 300 Diffusion Phase 500 boards 501 Metal / Alloy Body 120 Copper clip plating layer surface Aluminum surface on 140 Si chip

Claims

1. Metal particles having intermetallic compound crystals containing Sn, Cu, Ni, Al and Cr in a matrix containing Sn and a Sn-Cu alloy, The composition of the metal particles is Cu 0.7-15% by mass, Ni 1-0.02% by mass, Al 3-0.02% by mass, Cr 2-0.02% by mass, The balance is Sn (provided that, when unavoidable impurities are present, the unavoidable impurities are 0.1 mass% or less); The composition of the parent phase is Sn 92-99.9% by mass, Cu 5% by mass or less, Ni 1% by mass or less, Al is 3 mass% or less (however, when inevitable impurities are present, the inevitable impurities are 0.1 mass% or less); The composition of the intermetallic compound is Cu 5-50% by mass, Ni 6.5-0.1% by mass, Al 20-0.5% by mass, Cr 0.001-0.1% by mass, The balance is Sn (provided that, when unavoidable impurities are present, the unavoidable impurities are 0.1 mass% or less); The intermetallic compound crystals are present in the matrix.

2. A metal particle comprising:

2. A consolidated body comprising the metal particles according to claim 1.

Citation Information

Patent Citations

  • Solder composition and usage thereof

    JP1990034295A

  • Joined structure of solder joint

    JP2010274326A

  • Metal particle

    JP2018150614A

  • metal particles

    JP6799649B1

  • Bonding structure

    US20210078112A1

Cited By

  • Alloy ingots for bonding materials

    JP7849557B1